2006
DOI: 10.1055/s-2006-921420
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostik und präoperatives Staging des Endometriumkarzinoms mittels transvaginaler Sonographie - eine Übersicht

Abstract: Endometrial carcinoma is the most common malignant tumor of the female genital tract. The major non-invasive diagnostic method is ultrasound. Endometrial thickness (double layer) is measured by transvaginal sonography. The cut-off value in patients with postmenopausal bleeding is still controversial, although in patients with endometrial thickness below 4 mm (or 5 mm respectively), malignancy can be excluded with high probability. If the endometrium measures more than 4 mm (or more than 5 mm respectively) or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
1
3
0
2
Order By: Relevance
“…The value of TVUS in symptomatic premenopausal women and those using hormone substitution therapy is lower because the endometrial thickness regularly varies with changes of hormones during cycle. The data we obtained confirm previous findings which have shown that endometrial thickness above 5 mm in women with postmenopausal bleeding can be considered an accurate diagnostic parameter of endometrial malignancy [6]. However, there were no significant differences in endometrial thickness of pre-and postmenopausal women with endometrial carcinoma.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The value of TVUS in symptomatic premenopausal women and those using hormone substitution therapy is lower because the endometrial thickness regularly varies with changes of hormones during cycle. The data we obtained confirm previous findings which have shown that endometrial thickness above 5 mm in women with postmenopausal bleeding can be considered an accurate diagnostic parameter of endometrial malignancy [6]. However, there were no significant differences in endometrial thickness of pre-and postmenopausal women with endometrial carcinoma.…”
Section: Discussionsupporting
confidence: 89%
“…Good preoperative discrimination between benignant and malignant endometrial proliferations is essential for appropriate therapeutic approach. In postmenopausal women, vaginal bleeding and/or endometrial thickness measured by transvaginal ultrasonography above 5 mm are considered to be very suspicious of endometrial carcinoma and present an indication for exploratory curettage [6]. However, currently www.srpskiarhiv.rs there are no algorithms based on clinical, laboratory, and imaging parameters for the assessment of premenopausal women that may have endometrial carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Dietz et al claimed that the sensitivity and specificity of transvaginal ultrasonography were 92 and 50%, respectively, for predicting myometrial invasion in patients with endometrial cancer 14 . Ozdemir et al yielded the sensitivity and specificity of transvaginal ultrasonography as 86 and 90%, respectively, for predicting myometrial infiltration 15 .…”
Section: Discussionmentioning
confidence: 99%
“…In der Leitlinie Endometriumkarzinom der AGO wird dabei eine Endometriumdicke >5 mm als suspekt gewertet [7]. Andere Autoren sehen die Grenze bereits bei 4 mm [4,6]. Rien et al fanden, dass bei Patientinnen mit einer Postmenopausenblutung ohne Einnahme einer HRT und einer sonographischen Endometriumdicke von <4 mm zu 97% kein Karzinom vorlag.…”
Section: Endometriumkarzinomunclassified
“…Bei zunehmender sonographischer Endometriumdicke nahm dann das Karzinomrisiko mit jedem Millimeter um 22% zu [21]. Andere sonographische Befunde wie Struktur und Demarkierung des Endometriums sowie Abgrenzung zum Myometrium werden kontrovers diskutiert und sollten in jedem Fall in Kombination mit der Endometriumdicke gewertet werden [6]. Lediglich bei 1-maliger PMB und unauffälligem gynäkologischem Befund einschließlich unauffälliger Sonographie erscheint ein exspektatives Vorgehen mit kurzfristiger Kontrolle des Endometriums vertretbar.…”
Section: Endometriumkarzinomunclassified